Analysis of Factors Related with Compliance Taking Medicine of Leprosy in District Pragaan - Kiki Agustin Fatmala (Jurnal Berkala Epidemiologi, 2016)
The eradication of leprosy in several regions in Indonesia is still said to be slow. This is due to the knowledge, social and economic factors of the community in conducting Multi-Drug Therapy (MDT) treatment. Leprosy treatment is very important in the eradication of leprosy because leprosy can be cured by regular medical treatment. If the patient does not take medication regularly, the germs will be resistant to MDT so that symptoms will persist and may even worsen. This study aims to analyze the factors associated with adherence to take medication for leprosy patients in Pragaan Sub-District, Sumenep District. This study was an observational analytic study with cross-sectional study design. Data collection using interview techniques with questionnaire guidelines. The sample in this study were 40 people taken using simple random sampling technique. The relationship between the independent variables with the dependent variable is known through the Chi-square test with α = 0.05. The results showed that there was a relationship between knowledge (p = 0.01), family support (p=0.00), community stigma (p=0.00), the role of officers (p=0.01) and availability of drugs (p=0.00) with adherence to take leprosy. The conclusion that can be drawn is factors related to medication adherence, namely knowledge, family support, community stigma, the role of officers, and the availability of drugs. Effective counseling will provide motivation for sufferers to comply with medication.